Juridical Analysis of the Abuse of Kratom Herbal Plants According to Law Number 35 of2009 Concerning Narcotics - Kurniadi, Dani; F. Martono, Yacob; F Dewi, Yurika (Riviera Publishing, 2025)
The development of the use of the herbal plant kratom as an alternative medicine and fulfillment of health needs continues to increase, both at the national and global levels. One of the herbal plants that attracts attention is one of the plants originating from Southeast Asia, including Indonesia, Malaysia, and Thailand (Hassan Z et al. 2013). In Buntok City, South Barito Regency, Central Kalimantan Province, kratom has long been used as part of traditional medicine practices by the local community. UNODC (United Nations Office on Drugs and Crime) in 2013 classified kratom as New Psychoactive Substances, then the Food and Drug Supervisory Agency (BPOM) issued Circular Number in 2016 concerning the Prohibition of the Use of Mitragyna speciosa (kratom) in Traditional Medicine and Food Supplements which was later supported by the National Narcotics Agency. This means that kratom leaves were still not prohibited until 2022. This study aims to analyze the legal status of the herbal plant kratom (Mitragyna speciosa) which has psychoactive effects but has not yet been included in the narcotics category in Indonesia. Kratom has been traditionally used in several regions, but lately it has been misused as a psychoactive substance that causes narcotic-like effects. This study uses a normative juridical approach with qualitative methods, through literature studies, and interviews with legal experts and health practitioners. The results show that kratom has not been specifically regulated in Law Number 35 of 2009 concerning Narcotics, although it has the potential to be misused. The recommendation of this research is to strengthen regulations related to kratom, either through revisions to the narcotics law or the creation of special regulations.